Employee Voice and Job Satisfaction: An Application of Herzberg Two-factor Theory - Alfayad, Zaid; Arif, Lily Suriani Mohd (International Review of Management and Marketing, 2017)
The purpose of this empirical paper is to provide an understanding of the role of practicing employee voice in improving job satisfaction levels through the application of Herzberg two-factor theory. A cross-sectional design using a questionnaire was collected from 300 non-managerial employees at one of the largest private organizations in Jordan. Confirmatory factor analysis was executed to confirm the fitness of data to the proposed hypothesized model. Discriminant and convergent validity along with composite reliability were estimated to ensure the validity and the reliability of the instrument. Finally, structural equation modeling (SEM) by Amos was used to test the proposed hypothesis of the study. The findings reported a positive relationship between employee voice and job satisfaction. It indicates that the acknowledgment of employee voice creates a motivational environment which improves job satisfaction levels. Therefore, organizations need to reinforce and support employees' expression of ideas which may contribute to the growth of organizational effectiveness. Keywords: Employee Voice, Job Satisfaction, Herzberg Theory, Structural Equation Modelling JEL Classifications: M0, M12